El lenguaje de la arquitectura pública (2017)
"This work aims to describe the notion of the public inscribe in three contemporary buildings. Using deconstruction as a theoretical backdrop the Norman Foster?s Reichstag, Enric Miralles Scottish Parliament and Rafael Moneo?s Murcia Town Hall are read in order to understand what notion of the public is present in each of them. From that analysis a discursive theory of contemporary architecture is sketched." -- Tomado del Formato de Documento de Grado.